Nonfragile fault‐tolerant control of suspension systems subject to input quantization and actuator fault - Xiong, Jun; Chang, Xiao‐Heng; Park, Ju H.; Li, Zhi‐Min (International journal of robust and nonlinear control, 2020)
Summary This study addresses the quantized nonfragile feedback control problem for active suspension systems with and without actuator faults. By considering the input quantization, a class of dynamic quantizers is adopted. The multiplicative controller gain variation is used to describe the actuator parameter perturbation or uncertainty. Apart from the ride comfort, the road holding ability and the hard constraints on suspension deflection and actuator force are also taken into account, which can be treated as a multi‐objective control problem. The redundancy of input quantization error is used to formulate the quantized closed‐loop system via the descriptor representation approach, then a novel quantized control strategy based on state feedback by separately designing dynamic quantizer and controller is proposed for the closed‐loop system with and without actuator faults. The design strategy is a unified and simple one, then can be easily extended to the case of static output feedback, as only part of the variables measured by sensors are available, which avoids some equality constraints in existing works. Finally, some simulation results are presented to validate the feasibility and effectiveness of the developed control strategies.